2003
DOI: 10.1046/j.1365-3156.2003.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of childhood fevers with pre‐packaged antimalarial drugs in the home reduces severe malaria morbidity in Burkina Faso

Abstract: SummaryIn rural, malaria-endemic Burkina Faso, we evaluated the impact of the use of pre-packaged antimalarial drugs (PPAM), by mothers in the home, on the progression of disease in children from uncomplicated fever to severe malaria. In each village of one province, a core group of opinion leaders (mainly older mothers) was trained in the management of uncomplicated malaria, including the administration of PPAM. Full courses of antimalarial (chloroquine) and antipyretic (aspirin) drugs were packaged in agespe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
147
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(155 citation statements)
references
References 9 publications
4
147
3
1
Order By: Relevance
“…Although our results are not directly comparable with the study by Sirima et al, 22 because their study was retrospective and used a different treatment, both treatments tested in the present study were correlated with a lower incidence of severe malaria. The high prevalence of parasitaemia at day 28 in the ACT group could be a consequence of significant levels of amodiaquine resistance in this area.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discucontrasting
confidence: 99%
See 2 more Smart Citations
“…Although our results are not directly comparable with the study by Sirima et al, 22 because their study was retrospective and used a different treatment, both treatments tested in the present study were correlated with a lower incidence of severe malaria. The high prevalence of parasitaemia at day 28 in the ACT group could be a consequence of significant levels of amodiaquine resistance in this area.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discucontrasting
confidence: 99%
“…Among all severe malaria cases (see Table 2), none had coma or convulsions, a definition used in other similar studies. 22 No patients died in either group during the 28 days of follow-up.…”
Section: Clinical Efficacymentioning
confidence: 89%
See 1 more Smart Citation
“…7 Following the usual practice of assessing antimalarial treatments by outcome in the 28 days after diagnosis, we found that progress to severe malaria was 1.9% in children aged ≤5 years in both groups, and 0% among those aged >5years old, so that the incidence of severe malaria was kept to a lower level than reported in comparable studies of HMM. 8 However the AM and ACT groups were very different in terms of parasite clearance. The proportion of patients with parasitaemia at day 28 was 63-76% in the AM group and 21-49% in the ACT group (lower and upper estimates, P < 0.001 with both estimates).…”
Section: Introductionmentioning
confidence: 99%
“…One of the foremost strategies involves the introduction of communitybased management of malaria through the deployment of community health workers [2][3][4][5][6]. During the last decade, India's malaria control strategies under the aegis of the National Vector Borne Disease Control Programme (NVBDCP) introduced this strategy among other innovations to strengthen its fight against malaria [7] as the disease burden remains high -India continues to contribute around two-thirds of confirmed malaria cases in the South East Asia region of the World Health Organization [8].…”
Section: Introductionmentioning
confidence: 99%